The Effect Of Lemon (Citrus limon) Juice on Serum BUN And Creatiinin Levels In Hyperuricemia Rattus norvegicus - Siti Nofiani Mufida; Puspitasari Puspitasari (Medicra (Journal of Medical Laboratory Science/Technology), 2020)
Hyperuricemia is a condition of increasing levels of uric acid in blood serum above normal values. Citrus limon contains flavonoids which have the ability to regenerate kidney function and play a role in reducing oxidative stress. The purpose of this study is to determine the effect of lemon juice (Citrus limon) on serum BUN levels and creatinine in Rattus norvegicus rats that experienced hyperuricemia. The research design used is quantitative analysis using experimental methods. This study used 24 Rattus norvegicus rats were divided into 6 groups. group 1 as normal control, group 2 as hyperuricemia control, group 3 with chicken liver juice and allopurinol 10 mg / g BB, group 4 with chicken liver juice and lemon juice 0,9 ml / 200g BB, group 5 with giving chicken liver juice and lemon juice a dose of 1.8 ml / 200 g BB, group 6 with the administration of chicken liver juice and lemon juice with a dose of 3.6 ml / 200 g BB orally. White mice are taken blood for BUN (Blood Urea Nitrogen) and creatinine. Based on the results of the One Way ANOVA statistical test, there was an effect of Citrus limon juice on BUN levels in group 5 with a value of 18,425 mg/dl, while at creatinine levels which affected Citrus limon juice in group 5 of 0,250 mg/dl.